Juridical Analysis of Unregistered Marriages' Effects on Children's Legal Status and Civil Rights - Ismail, Rifki; Mustapa, Agil (Estudiante Law Journal, 2025)
Unregistered marriages, commonly known as Nikah Siri, remain widespread in Indonesia despite conflicting with formal legal norms. Although religiously valid, such marriages do not provide legal protection for women and children born from these unions. This paper aims to examine the legal consequences of unregistered marriages on the status and rights of children. Using a qualitative descriptive method with statutory and case study approaches, this research analyzes legal protections available to children from these marriages. The study finds that Constitutional Court Decision No. 46/PUU-VIII/2010 enables children born out of wedlock to establish civil relations with their biological fathers if scientifically proven. The findings reflect a shift in legal perspective toward a more humanistic and justice-oriented approach in protecting children’s rights.